Sintesis lapisan hydrophobic nanokomposit mangan oksida/polystyrene (MnO2/PS) untuk aplikasi self cleaning (Synthesis of manganese oxide / polystyrene nanocomposite hydrophobic coating (MnO2 / PS) for self cleaning applications ) - Tia Adriany Putri; - Ratnawulan; - Ramli (PILLAR OF PHYSICS, 2018)
The ability of a self-cleaning surface is widely used as a surface coating such as glass, buildings, textiles, ceramics, and so on. This mechanism is called self-cleaning. The self-cleaning mechanism of the hydrophobic substrate surface is based on the effect of the lotus leaf. The surface of the substrate with a lotus leaf effect makes the impurities accumulated on the surface of the substrate fall due to water repulsion. The purpose of this research is to investigate the synthesis of hydrophobic coating of MnO2 / PS nanocomposites which is expected to be utilized as a surface self-cleaning application. The result of this research is the synthesis of hydrophobic coating of MnO2 / PS nanocomposites shows a large change of contact angle. Where the contact angle increased during the temperature of 25-300 º C, then decreased to 400 ºC.